2016
DOI: 10.1186/s13013-016-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent idiopathic scoliosis (AIS): a multifactorial cascade concept for pathogenesis and embryonic origin

Abstract: This paper formulates a novel multifactorial Cascade Concept for the pathogenesis of adolescent idiopathic scoliosis (AIS). This Concept stems from the longitudinal findings of Clark et al. (J Bone Miner Res 29(8):1729-36, 2014) who identified leptin body composition factors at 10 years of age associated with a scoliosis deformity found at 15 years. We interpret these findings in the light of some concepts for AIS pathogenesis. In particular, we speculate that the leptin body composition effect is linked to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 40 publications
0
50
0
3
Order By: Relevance
“…In a population with AIS, body composition measurements such as BMI, fat-free mass, and fat mass index were lower than those in the general population [31]. Although the precise molecular mechanism remains to be elucidated, Burwell et al [32] hypothesized that lower leptin levels are related to the initiation of asynchronous neuro-osseous growth, leading to tension in the neuraxis and tethered anterior vertebral growth. In contrast, low BMI was not associated with scoliosis in man adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In a population with AIS, body composition measurements such as BMI, fat-free mass, and fat mass index were lower than those in the general population [31]. Although the precise molecular mechanism remains to be elucidated, Burwell et al [32] hypothesized that lower leptin levels are related to the initiation of asynchronous neuro-osseous growth, leading to tension in the neuraxis and tethered anterior vertebral growth. In contrast, low BMI was not associated with scoliosis in man adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…This is confirmed by some studies reporting that scoliotic children and adolescents had lighter body mass and greater height than normal adolescents of the same sex and age group (Wang, Wang, Zhu, Zhu, & Qiu, 2016;Ramírez et al, 2013). The anthropometric character of scoliosis patients is thought to be related to the pathophysiology of scoliosis, namely, the influence of leptin as well as somatic and autonomic nerve disharmony (Burwell et al, 2009;Burwell, Clark, Dangerfield, & Moulton, 2016).…”
Section: Introductionmentioning
confidence: 64%
“…As in the case of body height, our study also reported that scoliotic students had lower BMI than normal, but it was significant only in girls. Slenderness in scoliosis might be related to some mechanisms, pathophysiology of scoliosis involving leptin (Burwell et al, 2016;Liu et al, 2012), increased activity of the sympathetic nervous system (Burwell et al, 2009;Burwell et al, 2008a), and eating disorders (Smith, Latchford, Hall, Millner, & Dickson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers speculated that the decreased circulating leptin is linked to the onset of the imbalanced neuroosseous growth mechanism that leads to relative anterior skeletal overgrowth. This mechanism in combination with other factors ,including anatomical differences of vertebrae ,bipedal posture, growth acceleration during puberty, Hueter-Volkmann law and decreased bone mass leads to the development of IS 39 .…”
Section: Metabolic Factorsmentioning
confidence: 99%